Injection of platelet rich plasma for low backpain caused by lumbar disc degeneration: a prospective study - Shanmugam, M.; ., Shivakumar (International Journal of Research in Orthopaedics, 2020)
Background: Though the etiologies of chronic low back pain can be diverse, lumbar disc degeneration is one of the important causes of low backpain. In intractable cases of low back pain surgical interventions may be warranted. Intradiscal injection of platelet rich plasma is emerging as a novel treatment modality for chronic backpain and has been reported to have good results in terms of reduction of pain and improvement in functional abilities. Methods: This was a prospective study in which 30 patients with chronic low back pain were included. Platelet rich plasma was injected in nucleus pulposus of the affected part of lumbar spine under fluoroscopic control. Patients were followed up for 3 months. Reduction in severity of pain and functional improvement was assessed by Visual Analogue Scores (VAS) and Roland-Morris Low Back Pain and Disability Questionnaire (RDQ) scores. Results: The Mean age of the male patients was found to be 50.05±9.04 while the mean age of females was found to be 48.50±10.19. 18 (60%) patients were either overweight or obese. Remaining 12 (40%) patients had a normal BMI. The difference between mean VAS scores and RDQ scores at presentation and 3 months after PRP injection was found to be statistically highly significant (p<0.0001). Conclusions: The intradiscal injection of platelet rich plasma in patients with low back pain secondary to lumbar disc degeneration is effective in reducing back pain and causing significant functional improvement.